Iron-based magnetic absorbent with fluorescent corrosion early warning and self-repairing functions as well as preparation method and application of iron-based magnetic absorbent
By covering mesoporous silica on the surface of the iron-based magnetic absorber and loading a fluorescent indicator and metal corrosion inhibitor, the corrosion problem of iron-based magnetic absorber in harsh environments is solved, and the fluorescent corrosion warning and self-healing functions are realized, delaying the occurrence and development of corrosion.
Patent Information
- Application Number
- CN202411912168.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Iron-based magnetic absorbers are prone to corrosion in harsh environments such as high humidity and high salt, resulting in a decrease in absorbing performance. It is difficult for the existing technology to effectively warn and suppress initial corrosion.
Mesoporous silica is coated on the surface of the ferromagnetic alloy and loaded with fluorescent indicators and metal corrosion inhibitors. Mesoporous silica not only loads indicators and corrosion inhibitors, but also provides a barrier effect on corrosive media. Once corrosion occurs, the fluorescent indicator combines with Fe3+ ions to form a bright yellow fluorescent complex to warn of corrosion, and the metal corrosion inhibitor forms a dense protective film to prevent corrosion from continuing.
The fluorescent corrosion warning and self-healing function of iron-based magnetic absorbers is realized, which delays the occurrence and development of corrosion and improves the use effect in harsh environments.
Smart Images

Figure CN119724898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic absorbing materials, and in particular to an iron-based magnetic absorber with fluorescent corrosion early warning and self-repairing functions, and a preparation method and application thereof. Background Art
[0002] Absorbing materials can absorb and dissipate incident electromagnetic waves, providing stealth performance for equipment, so they are the focus of research. Iron-based magnetic absorbers have the advantages of high magnetic permeability and large magnetic loss, and are one of the commonly used electromagnetic wave absorbers. However, iron-based magnetic absorbers are prone to corrosion in harsh environments such as high humidity and high salt, which leads to a decrease in absorbing performance. At present, the demand for the use of absorbing materials in harsh environments is gradually increasing, and coping with the corrosion problem of iron-based magnetic absorbers has become an important research topic.
[0003] In the actual environment, corrosion mostly starts from pitting in micro areas, making it difficult to detect the occurrence of corrosion in the early stage. When rust spots appear on the coating surface, the material's wave absorption performance has been seriously damaged, which is very dangerous for the equipment. Therefore, corrosion should be controlled as early as possible. The current methods mainly include corrosion warning and self-repair. In the prior art, mesoporous silica is used to coat gallic acid to prepare smart nanocontainers. Gallic acid can react with Fe generated by corrosion. 3+ Ion coordination produces a lavender complex, so it can be used to warn of corrosion of iron-based materials. At the same time, the prior art uses hollow fibers to load metal corrosion inhibitors for self-repairing anti-corrosion coatings. When the coating is damaged, the corrosion inhibitor in the hollow fiber can be adsorbed on the metal surface to form a dense protective film, achieving a self-repairing anti-corrosion function. However, these methods are based on the research of conventional metal materials and cannot be directly applied to iron-based magnetic absorbents. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problem in the prior art that the corrosion of iron-based magnetic absorbers is difficult to detect and inhibit in the early stage. The present invention provides an iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions, and its preparation method and application. The method first coats mesoporous silica on the surface of a ferromagnetic alloy, and then loads a fluorescent indicator and a metal corrosion inhibitor into the mesoporous silica. In addition to the loading function, mesoporous silica can also provide a barrier effect on corrosive media. Once corrosion occurs, the fluorescent indicator will react with the Fe generated by the corrosion. 3+ The ions combine to form a bright yellow fluorescent complex to warn of corrosion; the metal corrosion inhibitor will be adsorbed on the surface of the corroded area to form a dense protective film, restoring the barrier effect against the corrosive medium.
[0005] The first object of the present invention is to provide a method for preparing an iron-based magnetic absorbent having fluorescent corrosion early warning and self-repairing functions, comprising the following steps:
[0006] Weigh the following components by mass: 60-80 parts of absorbent powder, 5-30 parts of silane, 0.5-4 parts of ammonia water, 0.5-3 parts of fluorescent indicator, and 1-5 parts of metal corrosion inhibitor;
[0007] Add absorbent powder, silane and ammonia water into a mixed solvent, mix and react, then add fluorescent indicator and metal corrosion inhibitor, stir and react, and then centrifuge and dry to obtain an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions.
[0008] Preferably, the absorbent powder is one of carbonyl iron, iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, iron-aluminum-boron alloy or amorphous alloy, iron-boron-phosphorus alloy or amorphous alloy, iron-nickel alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy;
[0009] The absorbent powder is in the shape of a sphere or a flake, and has a particle size of 3-40 μm.
[0010] Preferably, the fluorescent indicator is di[N,N'-bis(rhodamine B) lactam-ethyl]amine.
[0011] Preferably, the di[N,N'-bis(rhodamine B) lactam-ethyl]amine is prepared according to the following steps:
[0012] Rhodamine B hydrazide is dissolved in acetone, acetic acid is added as a catalyst, and the mixture is refluxed for 3-6 hours, followed by removal of the solvent under reduced pressure, and the residue is redissolved in chloroform, the chloroform solution is washed with deionized water, and dried over anhydrous sodium sulfate, and the chloroform is removed under reduced pressure, and the residue is recrystallized from anhydrous ethanol to obtain di[N,N'-bis(rhodamine B) lactam-ethyl]amine;
[0013] The mass ratio of the rhodamine B hydrazide to the acetic acid is (2-5):(0.1-2).
[0014] Preferably, the metal corrosion inhibitor is benzotriazole; and the silane is tetraethyl orthosilicate.
[0015] Preferably, the mixing reaction is stirred at 500-800 rpm and kept at 60-80°C for 3-6 hours; the stirring reaction is stirred at 500-800 rpm for 1-3 hours; the centrifugal drying is centrifuged at 8000-10000 rpm for 5-10 minutes, and then dried at 60-80°C for 10-14 hours.
[0016] Preferably, the mixed solvent is prepared from water and anhydrous ethanol;
[0017] Wherein, the mass ratio of the anhydrous ethanol to water is 1:1-8.
[0018] The second object of the present invention is to provide an iron-based magnetic absorbent with fluorescent corrosion early warning and self-repairing functions.
[0019] The third object of the present invention is to provide an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions for use in electromagnetic absorption.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention provides an iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions, and a preparation method and application thereof. The present invention aims at the problem that the corrosion of the iron-based magnetic absorber is difficult to detect and control in the early stage. First, silane is hydrolyzed, condensed and adsorbed on the surface of the iron-based magnetic absorber to coat mesoporous silica, and then the fluorescent indicator "FD1" and the metal corrosion inhibitor BTA are loaded by physical adsorption to prepare an iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions. The coated mesoporous silica is loaded with indicators and corrosion inhibitors on the one hand, and its dense structure and chemical inertness can also isolate the corrosive medium in the environment, play a barrier role, and delay the occurrence of corrosion; once the corrosive medium passes through the silicon layer and contacts the iron-based material, the FD1 indicator will react with the Fe generated by the corrosion. 3+ The ions combine to form a bright yellow fluorescent complex to warn of corrosion. At the same time, BTA will be adsorbed on the surface of the corrosion area to form a dense protective film to inhibit the further deterioration of corrosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the fluorescence emission view of each embodiment and comparative example after 1 hour of ultraviolet light irradiation. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments, but the embodiments are not intended to limit the present invention.
[0024] The present invention is aimed at iron-based magnetic absorbents, which are smaller in size than conventional metal materials and are usually embedded in resins when used, making their corrosion more difficult to detect and inhibit. Therefore, it is necessary to combine corrosion warning with self-repair and develop an early warning-self-repair anti-corrosion mechanism suitable for iron-based magnetic absorbents. Di[N,N'-bis(rhodamine B) lactam-ethyl]amine, also known as "FD1", is a fluorescent agent. The lactam group it contains can open the ring and react with Fe 3+The ions form a complex that emits bright yellow fluorescence under ultraviolet light. This property allows it to provide a more obvious corrosion warning effect. Benzotriazole (BTA) is a commonly used metal corrosion inhibitor that can be adsorbed on the metal surface to form a dense protective film and automatically repair the corroded damaged area. If the above two substances are used in combination, they can provide corrosion warning and self-repair capabilities for iron-based magnetic absorbers.
[0025] The purpose of the present invention is to provide an iron-based magnetic absorbent with corrosion early warning and self-repairing functions and a preparation method thereof in view of the problem that the corrosion of the iron-based magnetic absorbent is difficult to detect and inhibit in the early stage.
[0026] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an iron-based magnetic absorbent having fluorescent corrosion warning and self-repairing functions, comprising the following steps:
[0027] Weigh the following components by mass: 60-80 parts of absorbent powder, 5-30 parts of silane, 0.5-4 parts of ammonia water, 0.5-3 parts of fluorescent indicator, and 1-5 parts of metal corrosion inhibitor;
[0028] Add absorbent powder, silane and ammonia water into a mixed solvent, mix and react, then add fluorescent indicator and metal corrosion inhibitor, stir and react, and then centrifuge and dry to obtain an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions.
[0029] The present invention first coats the surface of the ferromagnetic alloy with mesoporous silica, and then loads the fluorescent indicator and metal corrosion inhibitor into the mesoporous silica. In addition to the loading function, the mesoporous silica can also provide a barrier to the corrosive medium. Once corrosion occurs, the fluorescent indicator will react with the Fe generated by the corrosion. 3+ The ions combine to form a bright yellow fluorescent complex to warn of corrosion; the metal corrosion inhibitor will be adsorbed on the surface of the corroded area to form a dense protective film, restoring the barrier effect against the corrosive medium.
[0030] Wherein, the absorbent powder is one of carbonyl iron, iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, iron-aluminum-boron alloy or amorphous alloy, iron-boron-phosphorus alloy or amorphous alloy, iron-nickel alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy;
[0031] The absorbent powder is in the shape of a sphere or a flake, and has a particle size of 3-40 μm.
[0032] The metal corrosion inhibitor is benzotriazole; and the silane is tetraethyl orthosilicate.
[0033] The mixed reaction is stirred at 500-800 rpm and kept at 60-80° C. for 3-6 hours; the stirring reaction is stirred at 500-800 rpm for 1-3 hours; the centrifugal drying is centrifuged at 8000-10000 rpm for 5-10 minutes, and then dried at 60-80° C. for 10-14 hours.
[0034] The mixed solvent is prepared from water and anhydrous ethanol;
[0035] Wherein, the mass ratio of the anhydrous ethanol to water is 1:1-8.
[0036] The fluorescent indicator is di[N,N'-bis(rhodamine B) lactam-ethyl]amine.
[0037] Specifically, the di[N,N'-bis(rhodamine B) lactam-ethyl]amine is prepared according to the following steps:
[0038] Rhodamine B hydrazide is dissolved in acetone, acetic acid is added as a catalyst, and the mixture is refluxed for 3-6 hours, followed by removal of the solvent under reduced pressure, and the residue is redissolved in chloroform, the chloroform solution is washed with deionized water, and dried over anhydrous sodium sulfate, and the chloroform is removed under reduced pressure, and the residue is recrystallized from anhydrous ethanol to obtain di[N,N'-bis(rhodamine B) lactam-ethyl]amine;
[0039] The mass ratio of the rhodamine B hydrazide to the acetic acid is (2-5):(0.1-2).
[0040] In one embodiment, the fluorescent indicator is di[N,N'-bis(rhodamine B) lactam-ethyl]amine, also known as "FD1", which is prepared by the following method:
[0041] 1) Dissolve 2-5 parts of rhodamine B hydrazide in 60-100 parts of acetone, add 0.1-2 parts of acetic acid as a catalyst, and reflux the mixed solution for 3-6 hours.
[0042] 2) Remove the solvent under reduced pressure and redissolve the residue in 50-80 parts of chloroform. Wash the chloroform solution with deionized water and dry it over anhydrous sodium sulfate.
[0043] 3) After removing the chloroform under reduced pressure, the residue is recrystallized from 60-80 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0044] In one embodiment, a method for preparing an iron-based magnetic absorbent having fluorescent corrosion warning and self-repairing functions specifically comprises the following steps:
[0045] Step 1: First, prepare 200-500 parts of a mixed solvent with deionized water and anhydrous ethanol, add 60-80 parts of absorbent powder, then add 5-30 parts of silane and 0.5-4 parts of ammonia water, stir evenly, and heat in a water bath to obtain dispersion A.
[0046] Step 2: Take 0.5-3 parts of fluorescent indicator and 1-5 parts of metal corrosion inhibitor, add them into dispersion A, stir and mix them thoroughly, and centrifuge and dry them to obtain an iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions.
[0047] The stirring rate in step 1 is 500-800 rpm; the water bath heating temperature is 60-80° C., and the heating time is 3-6 h.
[0048] In step 2, the stirring parameters are 500-800 rpm, 1-3 h; the centrifugal parameters are 8000-10000 rpm, 5-10 min; and the drying parameters are 60-80° C., 10-14 h.
[0049] The components in the following examples are all in parts by mass.
[0050] The second aspect of the present invention provides an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions.
[0051] A third aspect of the present invention provides an application of an iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions in electromagnetic absorption.
[0052] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0053] Example 1
[0054] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0055] Step 1: First, prepare 200 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:1, add 60 parts of carbonyl iron powder, then add 5 parts of TEOS and 2 parts of ammonia water, stir evenly at 500 rpm, and heat in a water bath at 80°C for 3 hours to obtain dispersion A.
[0056] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 1 hour, centrifuge at 8000 rpm for 10 minutes, and dry at 60°C for 14 hours to obtain a modified iron-based magnetic absorbent.
[0057] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0058] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0059] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0060] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0061] Example 2
[0062] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0063] Step 1: First, prepare 300 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 8:1, add 80 parts of Sendust powder, then add 15 parts of TEOS and 4 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 80°C for 4 hours to obtain dispersion A.
[0064] Step 2: Take 2 parts of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0065] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0066] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0067] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0068] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0069] Example 3
[0070] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0071] Step 1: First, prepare 300 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 6:1, add 80 parts of iron-silicon-chromium alloy powder, then add 10 parts of TEOS and 2 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 60°C for 6 hours to obtain dispersion A.
[0072] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 1 hour, centrifuge at 8000 rpm for 10 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0073] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0074] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0075] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0076] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0077] Example 4
[0078] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0079] Step 1: First, prepare 500 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:2, add 80 parts of iron-silicon alloy powder, then add 20 parts of TEOS and 3 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 80°C for 3 hours to obtain dispersion A.
[0080] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 10 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0081] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0082] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0083] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0084] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0085] Example 5
[0086] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0087] Step 1: First, prepare 200 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:2, add 60 parts of iron-aluminum-boron alloy or amorphous alloy powder, then add 10 parts of TEOS and 2 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 80°C for 4 hours to obtain dispersion A.
[0088] Step 2: Take 0.5 parts of fluorescent indicator and 4 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0089] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0090] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0091] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0092] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0093] Example 6
[0094] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0095] Step 1: First, prepare 500 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 8:3, add 80 parts of iron-boron-phosphorus alloy or amorphous alloy powder, then add 20 parts of TEOS and 4 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 80°C for 6 hours to obtain dispersion A.
[0096] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 10 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0097] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0098] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0099] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0100] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0101] Example 7
[0102] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0103] Step 1: First, prepare 200 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:1, add 60 parts of iron-nickel alloy powder, then add 10 parts of TEOS and 2 parts of ammonia water, stir evenly at 500 rpm, and heat in a water bath at 60°C for 4 hours to obtain dispersion A.
[0104] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0105] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0106] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0107] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0108] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0109] Example 8
[0110] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0111] Step 1: First, prepare 200 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:1, add 70 parts of iron-nickel-molybdenum alloy powder, then add 10 parts of TEOS and 2 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 80°C for 3 hours to obtain dispersion A.
[0112] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0113] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0114] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0115] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0116] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0117] Example 9
[0118] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0119] Step 1: First, prepare 300 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 8:3, add 70 parts of iron-chromium-nickel alloy powder, then add 10 parts of TEOS and 3 parts of ammonia water, stir evenly at 800 rpm, and heat in a water bath at 80°C for 3 hours to obtain dispersion A.
[0120] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0121] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0122] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0123] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0124] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0125] Example 10
[0126] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0127] Step 1: First, prepare 200 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:1, add 60 parts of iron-cobalt-chromium alloy powder, then add 5 parts of TEOS and 1 part of ammonia water, stir evenly at 500 rpm, and heat in a water bath at 60°C for 6 hours to obtain dispersion A.
[0128] Step 2: Take 0.5 parts of fluorescent indicator and 3 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 8000 rpm for 10 minutes, and dry at 60°C for 14 hours to obtain a modified iron-based magnetic absorbent.
[0129] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0130] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0131] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0132] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0133] Embodiment 11
[0134] A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions comprises the following steps:
[0135] Step 1: First, prepare 300 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:2, add 70 parts of iron-cobalt-nickel-chromium alloy powder, then add 10 parts of TEOS and 2 parts of ammonia water, stir evenly at 600 rpm, and heat in a water bath at 80°C for 3 hours to obtain dispersion A.
[0136] Step 2: Take 1 part of fluorescent indicator and 5 parts of BTA, add them to dispersion A, stir and mix at 800 rpm for 3 hours, centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0137] In step 2, the fluorescent indicator is FD1, which is prepared by the following method:
[0138] 1) Dissolve 5 parts of rhodamine B hydrazide in 80 parts of acetone, add 1 part of acetic acid as a catalyst, and reflux the mixed solution for 4 hours.
[0139] 2) The solvent was removed under reduced pressure, and the residue was redissolved in 80 parts of chloroform. The chloroform solution was washed with deionized water and dried over anhydrous sodium sulfate.
[0140] 3) After removing the chloroform under reduced pressure, the residue was recrystallized from 60 parts of anhydrous ethanol to obtain an almost colorless powder, which is the fluorescent indicator FD1.
[0141] Comparative Example 1
[0142] Step 1: First, prepare 200 parts of a mixed solvent with deionized water and anhydrous ethanol in a mass ratio of 5:1, add 60 parts of carbonyl iron powder, then add 5 parts of TEOS and 1 part of ammonia water, stir evenly at 800 rpm, heat in a water bath at 80°C for 3 hours, then centrifuge at 10000 rpm for 5 minutes, and dry at 80°C for 12 hours to obtain a modified iron-based magnetic absorbent.
[0143] At this point, the modified iron-based magnetic absorbent provided in the embodiments and comparative examples of the present invention is prepared.
[0144] In order to illustrate the corrosion warning and repair capabilities of the modified iron-based magnetic absorbent of the present invention, an equal amount of the modified iron-based magnetic absorbent prepared in each embodiment and comparative example was immersed in a 3.5wt.% NaCl solution to test the Fe 3+ The changes in ion concentration were observed; and ultraviolet light was used to irradiate the system to observe whether fluorescence was produced. The specific results are shown in Table 1 and Figure 1 shown.
[0145] Table 1 Fe of each embodiment and comparative example at different times 3+ Concentration and system fluorescence emission
[0146]
[0147] As shown in Table 1, Fe 3+ The presence of ions proves that the samples have been corroded. Figure 1 It can be seen that each example can show obvious bright yellow fluorescence in 1 hour, while the comparative example has no fluorescence phenomenon, indicating that the fluorescent indicator FD1 contained in the modified iron-based magnetic absorbent can react with Fe 3+ The ions generate bright yellow fluorescent complexes, thus providing an early warning of corrosion. 3+ The ion concentration at 6h and 12h was much lower than that of the comparative example, proving that only weak corrosion occurred in the example. This indicates that the BTA loaded in the modified iron-based magnetic absorbent repaired the corrosion damaged area and inhibited the further occurrence of corrosion.
[0148] In order to illustrate the performance of the modified iron-based magnetic absorbent, the modified iron-based magnetic absorbent prepared in each embodiment and comparative example was mixed with epoxy resin to prepare a coating, and the corresponding coating was prepared by spraying, as follows:
[0149] 70 parts of modified iron-based magnetic absorbent, 20 parts of epoxy resin, and 10 parts of polyamide curing agent were dispersed at 3000 rpm for 15 minutes using a stirring disperser, and then a certain amount of diluent was added to adjust the coating viscosity to 20-25 mPa·s, and stirring was continued at 3000 rpm for 15 minutes to obtain an absorbing coating.
[0150] The epoxy resin is a transparent viscous liquid, and is a product of Hubei Xinsihai Chemical Co., Ltd.
[0151] The polyamide curing agent is a medium-viscosity brown-yellow liquid, and is a product of Hubei Xinsihai Chemical Co., Ltd.
[0152] The diluent is prepared by mixing xylene and n-butanol in a mass ratio of 7:3. Both are colorless and transparent liquids and are products of Nanjing Hecheng Chemical Co., Ltd.
[0153] Subsequently, an absorbing coating with a thickness of 1 mm was prepared by compressed air spraying. The specific method is as follows: pour the coating into a W-71 spray gun, adjust the spraying pressure to 0.5 MPa, the spraying distance to 15-20 cm, the spray gun moving speed to 30-40 cm / s, and spray evenly on the surface of the substrate in an S-shaped path; after each 0.1 mm coating is sprayed, the sample is dried at room temperature for 10-15 minutes, and then the sample is placed in an oven and kept at 80°C for 12 hours to solidify the coating sprayed on the surface of the substrate, and the preparation process is repeated until the thickness of the obtained prefabricated layer reaches 1 mm.
[0154] In order to characterize the absorption capacity of the absorbing coating for electromagnetic waves, the reflection loss of the absorbing coating was tested by the bow method according to the GJB 2038-94 standard test. In order to verify the corrosion resistance of the absorbing coating, the absorbing coating was subjected to a 240h neutral salt spray test according to the GJB 150.11A-2009 standard, and then its absorbing performance was tested. The minimum reflection loss (RL min ) and effective absorption bandwidth (E A ) as shown in Table 2.
[0155] Table 2 Minimum reflection loss and effective absorption bandwidth of each embodiment and comparative example
[0156]
[0157] From the data in Table 2, it can be seen that the RL of the absorbing coating in each embodiment is min Value and EA After 240 hours of salt spray treatment, the RL of the absorbing coating in the comparative example decreased slightly. min Value and E A In conclusion, the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing function prepared in the embodiment of the present invention can well deal with the corrosion problem and effectively improve the use effect in harsh environment.
[0158] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions, characterized in that: The following steps are involved: Weigh the following components by mass: 60-80 parts of absorbent powder, 5-30 parts of silane, 0.5-4 parts of ammonia water, 0.5-3 parts of fluorescent indicator, and 1-5 parts of metal corrosion inhibitor; Add absorbent powder, silane and ammonia water into a mixed solvent, mix and react, then add fluorescent indicator and metal corrosion inhibitor, stir and react, and then centrifuge and dry to obtain an iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions.
2. The method for preparing the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions according to claim 1, characterized in that: The absorbent powder is one of carbonyl iron, iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, iron-aluminum-boron alloy or amorphous alloy, iron-boron-phosphorus alloy or amorphous alloy, iron-nickel alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy; The absorbent powder is in the shape of a sphere or a flake, and has a particle size of 3-40 μm.
3. The method for preparing the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions according to claim 1, characterized in that: The fluorescent indicator is di[N,N'-bis(rhodamine B) lactam-ethyl]amine.
4. The method for preparing the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions according to claim 3, characterized in that: The di[N,N'-bis(rhodamine B) lactam-ethyl]amine is prepared according to the following steps: Rhodamine B hydrazide is dissolved in acetone, acetic acid is added as a catalyst, and the mixture is refluxed for 3-6 hours, followed by removal of the solvent under reduced pressure, and the residue is redissolved in chloroform, the chloroform solution is washed with deionized water, and dried over anhydrous sodium sulfate, and the chloroform is removed under reduced pressure, and the residue is recrystallized from anhydrous ethanol to obtain di[N,N'-bis(rhodamine B) lactam-ethyl]amine; The mass ratio of the rhodamine B hydrazide to the acetic acid is (2-5):(0.1-2).
5. The method for preparing the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions according to claim 1, characterized in that: The metal corrosion inhibitor is benzotriazole; and the silane is tetraethyl orthosilicate.
6. The method for preparing the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions according to claim 1, characterized in that: The mixed reaction is stirred at 500-800 rpm and kept at 60-80° C. for 3-6 hours; the stirring reaction is stirred at 500-800 rpm for 1-3 hours; the centrifugal drying is centrifuged at 8000-10000 rpm for 5-10 minutes, and then dried at 60-80° C. for 10-14 hours.
7. The method for preparing the iron-based magnetic absorbent with fluorescent corrosion warning and self-repairing functions according to claim 1, characterized in that: The mixed solvent is prepared from water and anhydrous ethanol; Wherein, the mass ratio of the anhydrous ethanol to water is 1:1-8.
8. An iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions obtained by the method described in any one of claims 1 to 7.
9. Use of the iron-based magnetic absorber with fluorescent corrosion warning and self-repairing functions as claimed in claim 8 in electromagnetic absorption.
Citation Information
Patent Citations
Carbon steel corrosion inhibitor with fluorescence recognition function and applications thereof
CN103320119A
Porous amorphous soft magnetic composite wave-absorbing material and preparation method thereof
CN109554635A
Preparation method of corrosion-resistant wave-absorbing coating containing core-shell structure type magnetic absorbent
CN111001549A
Self-early-warning-self-repairing anticorrosive coating for steel and iron materials, and preparation method and repairing method thereof
CN113736326A
Corrosion self-early-warning coating material and preparation method thereof
CN116948453A